A Randomised Controlled Trial of a Caregiver-Facilitated Problem-Solving Based Self-Learning Program for Family Carers of People with Early Psychosis - Chien, Wai Tong (Int J Environ Res Public Health, 2020)
Facilitated self-help and problem-solving strategies can empower and support family carers to cope with caregiving for people with severe mental illnesses. This single-blind multi-site randomised controlled trial examined the effects of a five-month family-facilitated problem-solving based self-learning program (PBSP in addition to usual care), versus a family psychoeducation group program and usual psychiatric care only in recent-onset psychosis, with a six-month follow-up. In each of three study sites (integrated community centres for mental wellness), 114 people with early psychosis (≤5 years illness onset) and their family carers were randomly selected and allocated to one of three study groups (n = 38). Caregiving burden (primary outcome) and patients’ and carers’ health conditions were assessed at recruitment, and one-month and six-months post-intervention. Overall, 106 (94.7%) participants completed the assigned intervention and ≥1 post-test. Generalised estimating equations and subsequent contrast tests indicated that the PBSP participants showed significantly greater improvements in carers’ burden, caregiving experiences and problem-solving ability, and patients’ psychotic symptoms, recovery, and duration of re-hospitalisations over the six-month follow-up, compared with the other two groups (moderate to large effect size, η(2) = 0.12–0.24). Family-assisted problem-solving based self-learning programs were found to be effective to improve both psychotic patients’ and their carers’ psychosocial health over a medium term, thus reducing patients’ risk of relapse.